The social–psychological bases of anticonsumption attitudes - Zavestoski, Stephen (Psychology & Marketing, 2002)
Abstract This article proposes that the increasing number of individuals voluntarily reducing their levels of consumption may be motivated by underlying social–psychological stress related to living in a consumer society. Of the three primary motivational bases of the self (esteem, efficacy, and authenticity), it is argued that only self‐esteem and self‐efficacy can be acquired through consumption. The current growth of the voluntary simplicity movement, it is argued, is among those individuals who have met the need for esteem and efficacy through consumption, but have failed to achieve a sense of authenticity. Evidence from interviews with participants in the voluntary simplicity movement is presented in support of this proposition. Anticonsumption attitudes, it is concluded, result from a process of self‐inquiry triggered by the failure to feel authentic through one's consumption activities. Implications of anticonsumption attitudes in reaction to consumer culture are discussed. © 2002 John Wiley & Sons, Inc.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTAwMi9tYXIuMTAwMDc